Doxorubicin in combination with cisplatin, 5‐flourouracil, and vincristine is feasible and effective in unresectable hepatoblastoma: A Children's Oncology Group study. Issue 5 (11th November 2021) - Katzenstein, Howard M.; Malogolowkin, Marcio H.; Krailo, Mark D.; Piao, Jin; Towbin, Alexander J.; McCarville, M. Beth; Tiao, Gregory M.; Dunn, Stephen P.; Langham, Max R.; McGahren, Eugene D.; Finegold, Milton J.; Ranganathan, Sarangarajan; et al.
Abstract : Background: The Children's Oncology Group (COG) adopted cisplatin, 5‐flourouracil, and vincristine (C5V) as standard therapy after the INT‐0098 legacy study showed statistically equivalent survival but less toxicity in comparison with cisplatin and doxorubicin. Subsequent experience demonstrated doxorubicin to be effective in patients with recurrent disease after C5V, and this suggested that it could be incorporated to intensify therapy for patients with advanced disease. Methods: In this nonrandomized, phase 3 COG trial, the primary aim was to explore the feasibility and toxicity of a novel therapeutic cisplatin, 5‐flourouracil, vincristine, and doxorubicin (C5VD) regimen with the addition of doxorubicin to C5V for patients considered to be at intermediate risk. Patients were eligible if they had unresectable, nonmetastatic disease. Patients with a complete resection at diagnosis and local pathologic evidence of small cell undifferentiated histology were also eligible for an assessment of feasibility. Results: One hundred two evaluable patients enrolled between September 14, 2009, and March 12, 2012. Delivery of C5VD was feasible and tolerable: the mean percentages of the target doses delivered were 96% (95% CI, 94%‐97%) for cisplatin, 96% (95% CI, 94%‐97%) for 5‐fluorouracil, 95% (95% CI, 93%‐97%) for doxorubicin, and 90% (95% CI, 87%‐93%) for vincristine. Toxicity was within expectations, with death as a first event in 1 patient. The most common adverse events were febrile neutropenia (n = 55 [54%]), infection (n = 48 [47%]), mucositis (n = 31 [30%]), hypokalemia (n = 39 [38%]), and elevated aspartate aminotransferase (n = 28 [27%]). The 5‐year event‐free and overall survival rates for the 93 patients who did not have complete resection at diagnosis were 88% (95% CI, 79%‐93%) and 95% (95% CI, 87%‐98%), respectively. Conclusions: The addition of doxorubicin to the previous standard regimen of C5V is feasible, tolerable, and efficacious, and this suggests that C5VD is a good regimen for future clinical trials. Abstract : The addition of doxorubicin to the previous standard regimen of cisplatin, 5‐flourouracil, and vincristine is a feasible, tolerable, and efficacious novel treatment regimen (cisplatin, 5‐flourouracil, vincristine, and doxorubicin). This regimen is a reasonable option for future clinical trials, especially those including patients with unresectable disease at diagnosis.